A STUDY ON ETHOSOMES AS MODE FOR TRANSDERMAL DELIVERY OF AN ANTIPSORIATIC DRUG (CAHIERS MAGELLANES-NS, 2024)
The aim of the present research work is to prepare ethosome of Berberine chloride and to evaluate for vesicle shape, size, polydispersity index (PDI), zeta potential (ZP), entrapment efficiency (EE), and in vitro permeation studies. Berberine Chloride loaded nanosized ethosomes were prepared using hot method with varied concentrations of ethanol and soyaphosphotidylcholine (SPC). The prepared ethosomes were characterized by size, entrapment efficiency (EE), FT-IR, in vitro release, kinetic studies of in vitro release profile and stability study. The selected ethosomal formulation was incorporated in carbapol 934P for gel formation, and subsequently, evaluated for their physicochemical properties. The sizes of ethosomes were found to be in the range of 94. 07-297.11nm while PDI ranges from 0.261 to 1.53 and ZP was between −20.6 to−40.1 mV. Morphology studies showed unilamellar structure under transmission electron microscope and optical microscopy. The EE of ethosomes was found to be in the range of 42.5% to 90.01%. It may be concluded that a Berberine chloride loaded ethosomal delivery system for herbal medications is a promising technique.